Industrial water demand for agro-processing and beverage industries in Rwanda. Issue 1 (December 2016) - Munderere, Egide; Munyaneza, Omar; Wali, Umaru
Abstract Background Water play important role in industrial operation of food processing, such ingredient of the product, operation of equipment such as boilers, cooling towers, cleaning purposes to ensure a sufficient level of hygiene and food safety etc. Rwanda is rapidly developing and this development is associated with increase in population, urbanization, industrialization, modification of agricultural practices including rise in area of irrigated land etc. All these could cause increase in water uses and modification of water demand. Assessing future water demand of the country requires the understanding of specific water demand of different sectors mentioned above and its variation within those sectors. Growth of industrial sector is expected to rise in Rwanda especially because of the created enabling environment; this of cause will cause the rise in industrial water demand. In order to understand industrial water demand and be able to project it for the future it is necessary to know specific water demand of different type of industries in the country. However, there is no published evidence of this information country wide. It is therefore necessary to conduct industrial water demand assessment in the country. The main of this study is to quantify industrial water demand for different types of industries in Rwanda. Methods The data used for this study were obtained from records of various food processing industries and breweries, interviews and from relevant organizations such as Rwanda Development Board (RDB), Water and Sanitation Corporation (WASAC), Ministry of Trade (MINICOM), and National Institute of Statistics of Rwanda (NISR). Specific water demand for various products was estimated taking into consideration the amount of water used and quantity of product produced. Correlation method in MATHLAB was used to determine the relationship between water used and production. Results and discussion The results show that industrial water used for some industrial production in Rwanda is within the recommend limit example maize flour 2m3 /ton and breweries such as beer production industry 4 to 4.5 m3 /m3 and carbonate soft drink industries 4m3 /m3, as against internationally recommended water of 2m3 /ton, and 6.5 m3 /m3 respectively. However water uses for of the following, Sugar making industry 29/m3 /t, Meat processing industry 5/m3 /t and Tomato paste production industry 6 m3 /ton exceeded the internationally recommended which are 25/m3 /t, 2/m3 /t, 3.58 m3 /ton. Tomato Paste production industry shown strong relationship because as water demand is increasing also production is increasing. Thus from this linear model, about 98% of the variation in water demand can be explained by variation of tomato paste production due to high relationship between water demand and tomato paste production. Conclusions The quantity of water consumption differs between types of industries. It was revealed that the brewing industries uses more water than any other kind of industries in Rwanda this could related the amount of production and demand for the product. There is wide difference in specific water consumption between various industries. Brewery industries in Rwanda have shown best practice of water demand with specific water demand of 4 to 4.5 m3 /m3 of final product in which is less than the global bench mark of 6.5 m3 /m3 . Improvements need to be made in order to achieve the recommended best practice of three cubic meters of raw water for every cubic meter of carbonate soft drinks and four cubic meters of raw water for every cubic meter of beer produced.